2019
DOI: 10.18535/jmscr/v7i1.65
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lip Print Patterns among the People of Bihar

Abstract: Objectives: To determine the predominant lip print type in the Bihar population of India. Methods: In this cross -sectional study, 200 subjects of both sex (100 males and 100 females) aged between 25-40 years whose family origins were from Bihar were studied. Young adults without any disease related to lips, with normal lip mucosa were included in the study. The present study evaluates the pattern of lip print patterns among males and females and the findings of the study are compared with the available data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…Type Ia was more prevalent in females and Type Ib more in males. This finding was in contrast to the study carried out in India, done by Aman Mital et al 8 which reported Type IV lip pattern was most prevalent pattern in males (44%) and Type I was more in female. Similar finding was seen in study conducted by Sharma et al 9 and Verghese et al 10 which showed type-IV as predominant type in male and Type 1 in female.…”
Section: Discussioncontrasting
confidence: 98%
“…Type Ia was more prevalent in females and Type Ib more in males. This finding was in contrast to the study carried out in India, done by Aman Mital et al 8 which reported Type IV lip pattern was most prevalent pattern in males (44%) and Type I was more in female. Similar finding was seen in study conducted by Sharma et al 9 and Verghese et al 10 which showed type-IV as predominant type in male and Type 1 in female.…”
Section: Discussioncontrasting
confidence: 98%